(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Crude extract of leaves from Averrhoa carambola .L showed significant inhibition of growth and mutagenesis in Neurospora crassa. Result showed that 1 ml extract reacted with the test organism, N. crassa very much. During the period of 24 hours it gave only 2.4 cm linear vegetative growth of the mycelia. Whereas 0.5 ml and 0.25 ml extracts gave less reactions (1.75 cm and 2.25 cm respectively). The linear growth decreased with the increased of the concentration of the extracts. Conidia of Ema (5297) of N. crassa were treated for 3-4 hours separately in 100% and 50% concentration of the extracts. 100% extracts produced 4 types mutants namely ropy, albino, dirty and buff. 50% extracts produced 4 types of mutants namely- plug, vigorous, pigmented and conidial band. Key words: Neurospora crassa, Averrhoa carambola, mutants, ropy, albino, dirty, buff, plug, vigorous, pigmented and conidial band. Bangladesh J. Sci. Ind. Res. 42(4), 483-488, 2007